Transcriptoma da glândula de veneno do escorpião Tityus serrulatus no contexto de catálogos de transcritos de quelicerados - Erika Ramos de Alvarenga (2012)
The scorpion Tityus serrulatus belongs to the family Buthidae and is considered to be the most dangerous scorpion in Brazil, being responsible for several cases of envenomation. In this study, we performed a venom gland transcriptome analysis (1,629 ESTs), and compared it with transcript catalogues of 12 other Chelicerates to characterize the expression profile of scorpion venom glands. Beyond housekeeping transcripts specially related to protein synthesis, energy supply and structural functions, we found 35 different families of venompeptides or proteins in the cDNA library of T. serrulatus venom gland. These transcripts included three new complete sequences of toxins and more than a dozen putative venom gland proteins/peptides The venom glands had a clearly different distribution of Gene Ontology (GO) terms when compared to other types of glands or whole animal transcriptomes, due the predominance of GO terms such as "extracellular region", response to stimulus" and "channel regulators. The comparative transcriptomic revealed that some venom components were widely distributed throughout the Scorpiones order, others were exclusives to the Buthidae family, and some components were only identified in the Tityus genus. This study represented an advance towards understanding the T. serrulatus venom gland, and presented some potential bioactive peptides that could be exploited for biotechnological application. In addition, the comparative transcriptomic analysis revealed a particular expression profile for venom glands and the distribution of the main venom component families in different clades